Dampak Positif dan Negatif Pembelajaran Daring untuk Anak-Anak Dibawah Umur - Seli Nursafitri; Vina Kurnia Putri; Vindy Iq Refianty (Kampret Journal, 2022)
This research was conducted to see more clearly the impact that child’s receive due to drastic changes in the learning system in Indonesia since the Covid-19 pandemic. In the online learning process conducted in unison this certainly has a very impact on students who live it including children who should be more limited in their use in order to maintain the physical and psychic condition of the child.Therefore, we are working with parents to see how children are progressing in dealing with these changes in the learning system and how they see the impact of parenthood. From this we see that this online learning has a profound impact on the child's own life, either directly or indirectly and it depends on the economic condition of the family and the family's parenting patterns